A Brief Evaluation of an Interpretive, Self-Guided Mobile Tour. Issue 2 (November 2017) - Britt, Rebecca K.
In this brief report, an evaluation of a self-guided mobile tour was conducted at a new set of research facilities located at a university designed to attract two audiences: researchers and public visitors. A qualitative analysis using the think-aloud method was completed using the three types of devices through which visitors can complete the tour: a paper booklet, smartphone, or tablet. Findings from a college student sample demonstrated that the paper booklet was easier to use as opposed to the use of a tablet or smartphone. Participants discussed that paper booklets in guided tours offered the ability to take time to explore the landmarks and interpret the underlying meaning behind them. Suggestions are offered for future research on self-guided mobile tours based on research facilities.